Diseminasi Implementasi Kurikulum Merdeka Belajar pada Guru-Guru SMK Madani Makassar - Musdalifah; Prasetyo, Muh. Mulyadi; Sumarni AR; Yunus, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
One of the important tools that must be owned and mastered by teachers in the successful implementation of the Independent Curriculum is an understanding of the important elements in the Independent Learning Curriculum. The Merdeka Curriculum dissemination activity is part of the training activities for the implementation of the Independent Curriculum and the Learning Process in the Classroom, which is the result of a collaboration between Patompo University and SMK Madani Makassar. The implementation of the activity was carried out in the Makassar Madani Vocational School Hall on November 24 2022. The dissemination was carried out face to face with the target of class teachers at Madani Makassar Vocational School. The purpose of the dissemination is so that teachers are ready to use the Independent Curriculum with independent learning options. The implementation of the dissemination includes exposure to the components of the Independent Learning Curriculum, learning style quiz tests and reflection on the results of the learning style quiz tests so that the readiness of the Madani Vocational School Teachers in Makassar can be known.